Early Mesolithic Hunter–Gatherers and Landscape Acquisition by the Arctic Circle: The Ipmatis valley 7000 BC–1 AD - Bergman, Ingela; Zackrisson, Olle (Journal of Northern Studies, 2007)
Archaeological and palaeoecological studies in the Arjeplog area of northern Sweden have verified the arrival of hunter–gatherers soon after deglaciation. After modelling and subsequently surveying the reconstructed shorelines of tilted watercourses, Early Mesolithic settlements dating to 8600–8000 BP (14C years BP) were discovered. Makrosubfossil-, pollen- and charcoal analyses of peat stratigrafies and lake sediments corroborated that deglaciation was completed more than 1000 years earlier than has previously been postulated. Pollen records show that the early postglacial environment included complex plant communities lacking present day analogies, providing optimal subsistence conditions for the pioneer settlers. Studies of charcoal influx into lake sediments indicate that fires were more frequent than ever after, contributing to a productive natural environment. Regional studies in the Ipmatis valley in combination with in-depth analyses of selected archaeological sites, display that hunter–gatherers made the resources of the valley an integral part of their subsistence at an early stage. Landscape acquisition included not only the adjustment to existing conditions, but the actual manipulation of the environment. The interdisciplinary research approach has produced unique sets of archaeological and palaeoecological data. Results open new perspectives on human pioneer colonisation and landscape acquisition in relation to deglaciation and the development of postglacial ecosystems. The variety of methods applied sets a new standard for future research on early societies in sub-arctic regions.